Barbarian tides : 1500-600 BC - Time-Life Books (Amsterdam : Time-Life Books, 1991)
1. World history--1500-600 BC
Includes bibliographical references.
Bibliography: p. 170-171.
Basic Ed. Students
Keywords: Europe -- History -- To 476.